Deflection test evaluation of different lots of the same nickel-titanium wire commercial brand - Murilo Gaby Neves; Fabrício Viana Pereira Lima; Júlio de Araújo Gurgel; Célia Regina Maio Pinzan-Vercelino; Fernanda Soares Rezende; Gustavo Antônio Martins Brandão (Dental Press Editora, 2016)
Introduction: The aim of this in vitro study was to compare the elastic properties of the load-deflection ratio of orthodontic wires of different lot numbers and the same commercial brand. Methods: A total of 40 nickel-titanium (NiTi) wire segments (Morelli OrtodontiaTM - Sorocaba, SP, Brazil), 0.016-in in diameter were used. Groups were sorted according to lot numbers (lots 1, 2, 3 and 4). 28-mm length segments from the straight portion (ends) of archwires were used. Deflection tests were performed in an EMIC universal testing machine with 5-N load cell at 1 mm/minute speed. Force at deactivation was recorded at 0.5, 1, 2 and 3 mm deflection. Analysis of variance (ANOVA) was used to compare differences between group means. Results: When comparing the force of groups at the same deflection (3, 2 and 1 mm), during deactivation, no statistical differences were found. Conclusion: There are no changes in the elastic properties of different lots of the same commercial brand; thus, the use of different lots of the orthodontic wires used in this research does not compromise the final outcomes of the load-deflection ratio.